Usulan Dalam Mereduksi Kegagalan Untuk Perbaikan Kualitas Pada Industrial Automation - tosty maylangi sitorus (Universitas Islam Negeri Sultan Syarif Kasim Riau, 2021)
One of the leading automation companies in Indonesia is producing production to meet the needs of industrial automation or robot parts, and to meet the needs of companies using the linear guidance techniques available on 3D Printers. There is a noticeable difference in consumer behavior, where the quality of hand-held connectors is poor, which is reflected in the increase in the number of complaints that exceed the company's monthly limit. Using the process control statistics (SPC) method, cause and effect, and the 5W+1H method as in the previous study, the proposed improvements will be determined by the production of hand connectors on 3D Printers. Based on the results of the study, 2 points approached the control limit (UCL) on the P chart, which is the 5th and 10th observation data. This indicates that there is a mismatch in the product being produced. Causes of differentiation are derived based on the following factors: Engine (non-optimal machine condition); Methods (design work that requires new ideas to meet customer needs); Material (PLA does not meet standard and Expiration); Human (does not work according to SOP and employees are not in prime condition); Environment (high humidity level). The proposed improvement is obtained by the 5W + 1H method.Keywords: Quality Improvement, Industrial Automation, SPC, Cause and Effect Diagram, 5W+1H